FACTORS AFFECTING ENTREPRENEURIAL INTENTIONS AMONG COLLEGE STUDENT - Trisna Sary Lewaru (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2020)
ABSTRACT This study aims to analyze the factors that influence entrepreneurial intentions among college student. The five independent variables was used include need for achievement, locus of control, self-efficacy, instrumental readiness, entrepreneurship experience. Sample in this research is students on Pattimura University totaling 160 people. Multiple linear regression analysis was used to measure this study. The results of this study indicate that need for achievement, locus of control, entrepreneurship experience have no effect on the intentions of entrepreneurial among students. Whereas instrumental readiness and self-efficacy variable has positive and significant effect on entrepreneurial intention between students of Pattimura University. Keywords : Entrepreneurship, Intentions